2011
DOI: 10.5194/acp-11-1191-2011
|View full text |Cite
|
Sign up to set email alerts
|

The ice nucleation ability of one of the most abundant types of fungal spores found in the atmosphere

Abstract: Abstract. Recent atmospheric measurements show that biological particles are a potentially important class of ice nuclei. Types of biological particles that may be good ice nuclei include bacteria, pollen and fungal spores. We studied the ice nucleation properties of water droplets containing fungal spores from the genus Cladosporium, one of the most abundant types of spores found in the atmosphere. For water droplets containing a Cladosporium spore surface area of ∼217 µm 2 (equivalent to ∼5 spores with avera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 97 publications
6
105
2
Order By: Relevance
“…(Pouleur et al, 1992). In contrast to those findings is the recent research by Iannone et al (2011) that showed poor ice nucleation ability of Cladosporium spores, with immersion freezing starting at −28.5 • C. This might be due to the spores being coated with hydrophobic proteins that are widespread in filamentous fungi such as Cladosporium sp. Additionally, fungal aerosols are likely to be effective cloud condensation nuclei, but data on behalf of this is still scarce.…”
Section: Introductioncontrasting
confidence: 45%
“…(Pouleur et al, 1992). In contrast to those findings is the recent research by Iannone et al (2011) that showed poor ice nucleation ability of Cladosporium spores, with immersion freezing starting at −28.5 • C. This might be due to the spores being coated with hydrophobic proteins that are widespread in filamentous fungi such as Cladosporium sp. Additionally, fungal aerosols are likely to be effective cloud condensation nuclei, but data on behalf of this is still scarce.…”
Section: Introductioncontrasting
confidence: 45%
“…For example, by immersing ice nuclei in water droplets placed on a hydrophobic substrate surface and collecting a series of images at controlled cooling rates, the change in reflectivity and opacity following ice formation can be characterized, and the associated freezing conditions can be identified (e.g., Knopf and Alpert, 2013;Murray et al, 2011). More recently, other optical microscopy techniques coupled with a unique method of encapsulating particles into droplets followed by cooling (Iannone et al, 2011) or using the hydrophobic squalene/water emulsion were introduced to the community. Using a similar approach, substrate-supported cooling studies have been applied to determine the freezing temperature in the contact mode (e.g., Fornea et al, 2009;Niehaus et al, 2014), or of deposition nucleation (e.g., Kanji and Abbatt, 2006;Bingemer et al, 2012;Dymarska et al, 2006).…”
Section: State Of the Art Of In Measurement Techniquesmentioning
confidence: 99%
“…More recently, other optical microscopy techniques coupled with a unique method of encapsulating particles into droplets followed by cooling (Iannone et al, 2011) or using the hydrophobic squalene/water emulsion were introduced to the community. Using a similar approach, substrate-supported cooling studies have been applied to determine the freezing temperature in the contact mode (e.g., Fornea et al, 2009;Niehaus et al, 2014), or of deposition nucleation (e.g., Kanji and Abbatt, 2006;Bingemer et al, 2012;Dymarska et al, 2006). The microscopy-coupled substrate-supported freezing devices are advantageous for visualizing the consequences of specific ice nucleation modes in controlled and simulated environments.…”
Section: State Of the Art Of In Measurement Techniquesmentioning
confidence: 99%
“…For the operational conditions described from here on, the background due to container characteristics, water quality and working environment could become an issue at temperatures around −15 • C or lower. The employment of other methods based on different materials and smaller volume quantities is then recommended to investigate colder temperature intervals, simultaneously allowing the detection of higher abundance of ice nucleators with a reduced background (for instance, Iannone et al, 2011).…”
Section: Description Of the Apparatus (Linda)mentioning
confidence: 99%